Muscle activity in giant slalom. A case study of an elite skier - Gantenbein, C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Insights into the biomechanical processes and muscle control in alpine skiing are of particular importance in order to improve the quality of the movement, to prevent injury, to sift talents or to optimize training recommendations (Turnbull, Kilding, & Keogh, 2009). Due to the lack of current data on muscle activity patterns in elite ski racers since the carving technology has been invented, the present study shows the relationship between the driving technique and muscle activity patterns that occur. Method: In the following pilot study, a Swiss elite athlete took part from the discipline Alpine Skiing (Junior World Champion 2009 in the combination). Hip and knee angles were recorded and EMG activity of 12 muscles was derived on the right side of the body during four giant slalom races in a medium steep terrain. For the EMG analysis, the wavelet method according to von Tscharner was used (von Tscharner, 2000). Results: The average hip and knee angle at the outer leg (. 44 ± 2 °, respectively 43 ± 1 °) is significantly smaller than the inner leg (65 ± 2 °, respectively 81 ± 3 °, extended leg = 0 °.). The average angular velocity at the outer leg at the knee is 69 ± 3 ° / s during knee extension and at the inner leg 84 ± 8 ° / s during knee flexion. The M. vastus lateralis and M. vastus medialis show activity during the swing phase on the outer leg and the M. rectus femoris is active while the inner leg phase. The M. biceps femoris shows activity during the outside leg phase and the M. semitendinosus while the inner leg phase. At the beginning of a turn, it shows a visible preactivation of the hamstrings compared to quadriceps muscles. Conclusion: During giant slalom races, knee angular velocities are rather low. Unilateral activation of the muscles M. vastus lateralis and M. vastus medialis at the outer leg and an activation of the M. recuts femoris at the inner leg indicate that the M. quadriceps is not activated synchronously in regular competitive skiing. Differences in activity patterns of the hamstrings show the great importance of the rotational stability of the lower extremity in competitive skiing. The results confirm the great importance of a function-specific training of knee extensors and flexors muscles in alpine ski racing.